Outcomes and Complications in a Case Series of 39 Total Laparoscopic Prophylactic Gastropexies Using a Modified Technique - Veronica Giaconella (Animals, 2021)
Laparoscopic-assisted, laparoscopic, and endoscopic gastropexy techniques have been proven successful in recent years. Thanks to minimal invasiveness, low morbidity, and fast recovery, total laparoscopic gastropexy techniques have been gaining popularity. The objective of this study was to describe the use of a modified minimally invasive technique to perform prophylactic gastropexy in dogs. A case series study of 39 client-owned dogs was undertaken from June 2019 to August 2020. Each dog underwent total laparoscopic prophylactic gastropexy using a simple continuous barbed suture line and two laparoscopic needle holders without incising the seromuscular layer of the stomach and the abdominal wall. Surgical time, the number of stitches, and the length of suture were recorded. Telephone checks, owner questionnaires, and ultrasonographic exams were used to evaluate the effectiveness of the procedure after surgery. The median gastropexy surgical time was 12 min (range 4–30 min), and the median length of the suture line was 3 cm (range 2–4 cm). The last follow-up check was carried out 9 months (mean, range 3–14 months) after surgery, and all ultrasonographic exams (n = 29) showed an intact gastropexy. Intraoperative and postoperative complications were noted. This total laparoscopic gastropexy technique was found to be safe, fast, simple, and with a low morbidity rate. It appears to be a new alternative to other methods of prophylactic gastropexy; however, further research in this area is warranted.